Impacts of perceived justice, workplace fun on innovative work behavior and job performance of lecturers at universities in Ho Chi Minh City - Nguyen, Thi Kim Ba; Le, Thi Thanh Truc; Tran, The Nam; Ho, Thi Thanh Thuy; Chau, My Chi (Journal of Finance - Marketing Research, 2023)
Innovative behavior, which is primarily leading to the enhancement of lecturer performance, is an ongoing process that lecturers embrace when being assigned the strategic role in enhancing education quality. An effectively operating performance process is crucial, considering the challenging and demanding nature of the teaching profession. Drawing on organizational theory and theory of planned behavior, authors propose that when teachers have fun at work and perceive different forms of justice in their institutions, they will feel more respected, energetic and tend to produce higher levels of innovative behavior and better performance in their job. To assess the study hypotheses, data were collected from 152 lecturers who work in public universities in Ho Chi Minh City and analyzed using Partial least squares structural equation modeling (PLS-SEM). The results show that “job performance” of lecturers is only affected by “workplace fun” while “innovative work behavior” is positively influenced by the two factors “perceived justice” and “fun at work,” and lecturers’ innovation is in turn positively related to their job performance. In theory, accepted hypotheses support organizational theory and the theory of planned behavior. In practice, university authorities should provide more fun at the workplace for lecturers. Moreover, justice must be maintained and improved in organizations